Bridging tradition and innovation: how music is taught in Malaysian primary schools - Ong, Peter (College of Creative Arts, 2025)
This study examines the challenges and opportunities in implementing music education in Malaysian primary schools from traditional and innovative teaching perspectives. Employing a qualitative research design, semi-structured interviews were conducted with five music education experts selected for their extensive experience in teaching, curriculum design, and educational theory. The findings identify three primary challenges: (1) a shortage of qualified music teachers, particularly in rural areas; (2) limited budget allocation and institutional support for music programs; and (3) insufficient integration of technological tools in music instruction. The study highlights effective strategies that combine traditional and contemporary approaches, such as blending Malaysian folk music with modern styles, adopting movement-based learning techniques, and incorporating technology to enhance music education. Experts emphasize the need for comprehensive teacher training, increased funding for resources, and a curriculum that balances the preservation of cultural heritage with technological innovation. This research contributes valuable empirical insights to the discourse on music education reform in Malaysia, offering guidance for policy development and implementation.